1993
DOI: 10.1177/089875649301000204
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Effectiveness of Clindamycin in Diseases of the Oral Cavity

Abstract: Veterinary dental ultrasonic equipment can cause bacteria to be aerosolized during prophy procedures. Preoperative treatment with clindamycin prior to removal of calculus using an ultrasonic scaler can reduce aerosolized bacteria. Reduction of plaque bacteria was assessed and was statistically significant in those patients receiving clindamycin. This article describes the evaluation and results of clindamycin application when given prior to dental prophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In all advanced cases of periodontal disease, appropriate dental care should be undertaken to avoid further disease development. It has been reported that P. gulae is susceptible to clindamycin, which has been approved for the treatment of periodontal disease in dogs ( 14 , 15 ). Recently, our group showed that combination therapy using clindamycin and IFN-α treatment can improve periodontal condition and reduce P. gulae in dogs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In all advanced cases of periodontal disease, appropriate dental care should be undertaken to avoid further disease development. It has been reported that P. gulae is susceptible to clindamycin, which has been approved for the treatment of periodontal disease in dogs ( 14 , 15 ). Recently, our group showed that combination therapy using clindamycin and IFN-α treatment can improve periodontal condition and reduce P. gulae in dogs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effects of clindamycin on growth of P. gulae strains. Clindamycin has been used for the treatment of periodontal disease in dogs 19 . Therefore, we analysed whether clindamycin was effective for P. gulae with each fimA genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic therapy is commonly used as part of the treatment for canine periodontal disease. According to previous studies, preoperative treatment with clindamycin prior to removal of calculus using an ultrasonic scaler can reduce aerosolized bacteria [23] . In our study, in spite of the previous antibiotherapy in some patients, strong bacterial contamination of the released aerosols was still present, suggesting that antibiotherapy per se is not a warranty of less contaminated aerosols.…”
Section: Discussionmentioning
confidence: 99%